Granulomatous lymphocytic interstitial lung disease: limiting immunosuppressive therapy—a single‐centre experience. Issue 5 (5th May 2020) - Beaton, Thomas J.; Gillis, David; Morwood, Karen; Bint, Michael
Abstract: Granulomatous lymphocytic interstitial lung disease (GLILD) is characterized by lymphocytic and granulomatous pulmonary infiltration occurring in common variable immunodeficiency (CVID). It is associated with increased mortality compared with CVID patients without GLILD. There are no treatment guidelines due to the low prevalence and the heterogeneity of the condition. A case review of three patients diagnosed with GLILD was performed from a single Australian centre. Patients met the European Society of Immunodeficiency criteria for CVID and a diagnosis of GLILD was confirmed by a multidisciplinary team. Patients were managed with immunoglobulin (Ig) replacement and immunosuppressive agents if required: the decision for immunosuppression was made on the basis of symptoms and declining pulmonary function. All patients clinically improved. One patient had immunosuppressive treatment ceased. GLILD responds to varying immunosuppressive regimes when IgG monotherapy fails. Immunosuppressive therapy can be discontinued following improvement, but patients require close observation. This series helps inform future GLILD treatment guidelines. Abstract : Granulomatous lymphocytic interstitial lung disease (GLILD) can be a progressive ILD‐associated common variable immunodeficiency (CVID) that results in increased mortality. There are no treatment guidelines; however, progressive disease often responds to immunosuppression when intravenous immunoglobulin g (IVIg) monotherapy fails. This series adds evidence that immunosuppression can be limited with close observation in clinically stable patients and some patients can consider ceasing immunosuppression when disease has initially responded.